Cardiomyopathy Is Associated with Ribosomal Protein Gene Haplo-Insufficiency in Drosophila melanogaster. - Casad, M.E.; Abraham, D.; Kim, I.M.; Frangakis, S.; Dong, B.; Lin, N.; Wolf, M.J.; Rockman, H.A. (Genetics, 2011)
The Minute syndrome in Drosophila melanogaster is characterized by delayed development, poor fertility, and short slender bristles. Many Minute loci correspond to disruptions of genes for cytoplasmic ribosomal proteins, and therefore the phenotype has been attributed to alterations in translational processes. Although protein translation is crucial for all cells in an organism, it is unclear why Minute mutations cause effects in specific tissues. To determine whether the heart is sensitive to haplo-insufficiency of genes encoding ribosomal proteins, we measured heart function of Minute mutants using optical coherence tomography. We found that cardiomyopathy is associated with the Minute syndrome caused by haplo-insufficiency of genes encoding cytoplasmic ribosomal proteins. While mutations of genes encoding non-Minute cytoplasmic ribosomal proteins are homozygous lethal, heterozygous deficiencies spanning these non-Minute genes did not cause a change in cardiac function. Deficiencies of genes for non-Minute mitochondrial ribosomal proteins also did not show abnormal cardiac function, with the exception of a heterozygous disruption of mRpS33. We demonstrate that cardiomyopathy is a common trait of the Minute syndrome caused by haplo-insufficiency of genes encoding cytoplasmic ribosomal proteins. In contrast, most cases of heterozygous deficiencies of genes encoding non-Minute ribosomal proteins have normal heart function in adult Drosophila.